Twenty steps for developing a healthy cities project (WHO CopenhagenDK, 1992)
Provides guidance and a reference framework for cities that are in the process of introducing a Healthy Cities Project, or are reviewing and expanding an existing one. Describes the three phases of development: the starting up process, project organisation and areas for action and strategic work.
DC